Ezrin, a plasma membrane–microfilament linker, signals cell survival through the phosphatidylinositol 3-kinase/Akt pathway - Gautreau, Alexis (The National Academy of Sciences, 1999)
ERM (Ezrin–Radixin–Moesin) proteins function as plasma membrane–actin cytoskeleton linkers and participate in the formation of specialized domains of the plasma membrane. We have investigated ezrin function in tubulogenesis of a kidney-derived epithelial cell line, LLC-PK1. Here we show that cells overproducing a mutant form of ezrin in which Tyr-353 was changed to a phenylalanine (Y353F) undergo apoptosis when assayed for tubulogenesis. While investigating the mechanism responsible for this apoptosis, we found that ezrin interacts with p85, the regulatory subunit of phosphatidylinositol 3-kinase (PI 3-kinase). Two distinct sites of ezrin are involved in this interaction, the amino-terminal domain containing the first 309 aa and the phosphorylated Tyr-353 residue, which binds to the carboxyl-terminal SH2 domain of p85. Cells producing Y353F ezrin are defective in activation of the protein kinase Akt, a downstream target of PI 3-kinase that protects cells against apoptosis. Furthermore, the apoptotic phenotype of these cells is rescued by production of a constitutively activated form of PI 3-kinase. Taken together, these results establish a novel function for ezrin in determining survival of epithelial cells by activating the PI 3-kinase/Akt pathway.